Connective Action and Digital Activity of The Cipayung Group in Protesting The Increase of Fuel Price - Yosua Abib Mula Sinurat (PERSPEKTIF, 2023)
Students who are members of the Kelompok Cipayung organization have not received special attention from academics, especially for their contribution to the establishment of a good citizen. This study discusses how the digital activities carried out by Kelompok Cipayung on social media. The method in this study uses a qualitative descriptive approach with the theoretical framework of connecting action by Bennett and Segerberg. By using content analysis and social media analysis, the research focuses on protests by students of Kelompok Cipayung against the case of rising fuel prices in October 2022. The results of the analysis obtained show that the social protests that appear on social media are a response to the critical economic conditions that are currently happening. In addition, protests that appear on social media have the same period, have similar narratives, and are not directly binding, both between organizations and individuals. Other findings also show that the strategy and objectives of the protests need to be managed transparently.